Critical Role of the PA-X C-Terminal Domain of Influenza A Virus in Its Subcellular Localization and Shutoff Activity - Hayashi, Tsuyoshi (J Virol, 2016)
PA-X is a recently identified influenza virus protein that is composed of the PA N-terminal 191 amino acids and unique C-terminal 41 or 61 residues. We and others showed that PA-X has a strong ability to suppress host protein synthesis via host mRNA decay, which is mediated by endonuclease activity in its N-terminal domain (B. W. Jagger, H. M. Wise, J. C. Kash, K. A. Walters, N. M. Wills, Y. L. Xiao, R. L. Dunfee, L. M. Schwartzman, A. Ozinsky, G. L. Bell, R. M. Dalton, A. Lo, S. Efstathiou, J. F. Atkins, A. E. Firth, J. K. Taubenberger, and P. Digard, 2012, Science 337:199–204, http://dx.doi.org/10.1126/science.1222213, and E. A. Desmet, K. A. Bussey, R. Stone, and T. Takimoto, 2013, J Virol 87:3108–3118, http://dx.doi.org/10.1128/JVI.02826-12). However, the mechanism of host mRNA degradation, especially where and how PA-X targets mRNAs, has not been analyzed. In this study, we determined the localization of PA-X and the role of the C-terminal unique region in shutoff activity. Quantitative subcellular localization analysis revealed that PA-X was located equally in both cytoplasm and nucleus. By characterizing a series of PA-X C-terminal deletion mutants, we found that the first 9 amino acids were sufficient for nuclear localization, but an additional 6 residues were required to induce the maximum shutoff activity observed with intact PA-X. Importantly, forced nuclear localization of the PA-X C-terminal deletion mutant enhanced shutoff activity, highlighting the ability of nuclear PA-X to degrade host mRNAs more efficiently. However, PA-X also inhibited luciferase expression from transfected mRNAs synthesized in vitro, suggesting that PA-X also degrades mRNAs in the cytoplasm. Among the basic amino acids in the PA-X C-terminal region, 3 residues, 195K, 198K, and 199R, were identified as key residues for inducing host shutoff and nuclear localization. Overall, our data indicate a critical role for the 15 residues in the PA-X C-terminal domain in degrading mRNAs in both the cytoplasm and nucleus. IMPORTANCE Influenza A viruses express PA-X proteins to suppress global host gene expression, including host antiviral genes, to allow efficient viral replication in infected cells. However, little is known about how PA-X induces host shutoff. In this study, we showed that PA-X localized equally in both the cytoplasm and nucleus of the cells, but the nuclear localization of PA-X mediated by its C-terminal region has a significant impact on shutoff activity. Three basic residues at the C-terminal region play a critical role in nuclear localization, but additional basic residues were required for maximum shutoff activity. Our findings indicate that PA-X targets and degrades mRNAs in both the nucleus and cytoplasm, and that the first 15 residues of the PA-X unique C-terminal region play a critical role in shutoff activity.